Characterization and source identification of fine particulate matter in urban Beijing during the 2015 Spring Festival - Ji, Dongsheng; Cui, Yang; Li, Liang; He, Jun; Wang, Lili; Zhang, Hongliang; Wang, Wan; Zhou, Luxi; Maenhaut, Willy; Wen, Tianxue; Wang, Yuesi (Elsevier, 2018)
The Spring Festival (SF) is the most important holiday in China for family reunion and tourism. During the 2015 SF an intensive observation campaign of air quality was conducted to study the impact of the anthropogenic activities and the dynamic characteristics of the sources. During the study period, pollution episodes frequently occurred with 12 days exceeding the Chinese Ambient Air Quality Standards for 24-h average PM2.5 (75 μg/m3), even 8 days with exceeding 150 μg/m3. The daily maximum PM2.5 concentration reached 350 μg/m3 while the hourly minimum visibility was <0.8 km. Three pollution episodes were selected for detailed analysis including chemical characterization and diurnal variation of the PM2.5 and its chemical composition, and sources were identified using the Positive Matrix Factorization model. The first episode occurring before the SF was characterized by more formation of SO42− and NO3− and high crustal enrichment factors for Ag, As, Cd, Cu, Hg, Pb, Se and Zn and seven categories of pollution sources were identified, whereby vehicle emission contributed 38% to the PM2.5. The second episode occurring during the SF was affected heavily by large-scale firework emissions, which led to a significant increase in SO42−, Cl−, OC, K and Ba; these emissions were the largest contributor to the PM2.5 accounting for 36%. During the third episode occurring after the SF, SO42−, NO3−, NH4+ and OC were the major constituents of the PM2.5 and the secondary source was the dominant source with a contribution of 46%. The results provide a detailed understanding on the variation in occurrence, chemical composition and sources of the PM2.5 as well as of the gaseous pollutants affected by the change in anthropogenic activities in Beijing throughout the SF. They highlight the need for limiting the firework emissions during China's most important traditional festival.